Tool-Use Training Induces Changes of the Body Schema in the Limb Without Using Tool - Sun, Yu; Tang, Rixin (Frontiers in Human Neuroscience, 2019)
Previous studies have shown that tool use affects the plasticity of the body schema, that is, people will perceive the tool as a part of their body and thus feel like they have "longer limbs" after using tools. However, it is unclear whether tool embodiment could spread to untrained limbs and whether the proprioception of one limb could be utilized by other limbs. Two experiments were conducted to solve these problems. We asked blindfolded participants either to find the target object with a cane (Experiment 1A) or to walk with a cane (Experiment 1B). We compared the estimated tactile distance before and after tool use training. In the Experiment 1A, the results illustrated that the tactile perception of the forearm was prolonged after tool use, while other body parts didn’t change significantly, which implied that the body schema could change merely by relying on proprioception and that tool morphology constrains the plasticity of the body schema. In Experiment 1B, the untrained foot and calf extended significantly after tool-use, but the trained hand and forearm did not extend. In Experiment 2, we found no changes in the body schema of foot when participants were trained to walk blindfolded without a cane. These results indicated that the proprioception information of one limb could be exploited by another limb to extend the body schema even though that limb was not trained.